Highly improved performance of ZnII tetraarylporphyrinates in DSSCs by the presence of octyloxy chains in the aryl rings. Issue 6 (23rd December 2014) - Orbelli Biroli, A.; Tessore, F.; Vece, V.; Di Carlo, G.; Mussini, P. R.; Trifiletti, V.; De Marco, L.; Giannuzzi, R.; Manca, M.; Pizzotti, M.
Abstract : The presence of octyloxy chains in the o, o -, o, p - or o -positions, instead of bulky t -butyl groups at the m -positions of the four phenyl groups of β-substituted Zn II -tetraarylporphyrinate dyes, improves the power conversion efficiency in DSSCs. Abstract : Three new β-substituted Zn II -tetraarylporphyrinate dyes (1–3 ), bearing octyloxy chains at the o, o -, o, p - or o -positions of the four phenyl groups respectively, were synthesized, characterized and investigated as sensitizers for DSSCs. In particular, the alkoxy group position strongly influences their electronic absorption and electrochemical features. Improvements in power conversion efficiency ranging from 40% to 80% were obtained with respect to a reference dye (4 ) characterized by the presence of sterically bulky t -butyl groups at the m -positions.